Fighters pilot helmet design for 5th generation aircraft - McAndrew, Ian; Moran, Katherine; Little, Andrew (Cranfield University Press, 2013)
Fighter pilots’ helmets have become more complex and heavier resulting in long term implications to pilots musculoskeletal systems as they fly and experience high g-load. Current research has identified design changes to the helmet to accommodate the ancillary items fitted to assist pilots but at the expense of comfort and additional loading. Its manufacturing requirements and adaptations to offer bespoke solutions are addressed to allow for training and operational usage. To produce the next generation of helmets that reduce long-term injuries, from g-loads and asymmetrical ancillaries requires individual considerations, unique manufacturing requirements and the ability to support with service spares anywhere in the world at short notice. This paper will describe how manufacturing requirements are matched to ergonomic needs and bespoke components can support global demands.
Keywords: Pilot helmets; Bespoke manufacture; Global support